Fritz Saxl - Eine Biografie Aby Warburgs Bibliothekar und erster Direktor des Londoner Warburg Institutes - McEwan, Dorothea (2013)
Aby Warburg (1866-1929), the celebrated Hamburg art historian, who broke new ground with his research into Renaissance art history, found in Fritz Saxl (1890-1948), art historian, head librarian and finally his successor as director of Warburg's library and later the Warburg Institute, a scholar who contributed to the shaping of a pluridisciplinary understanding of research. Through Saxl's research of problems of Late Antiquity and the Middle Ages he gave important impulses to the scholarly understanding of intellectual history. Saxl, who extended the library system of the "good neighbourliness" of books, demonstrated his organizational thinking and strategies, which anticipated the use of hyperlinks - albeit without today's electronic technology. It was Saxl who turned Warburg's library from a private library into the centre of an international network for scholars. He spoke of himself as the wanderer through the museums and libraries of Europe, an agricultural worker who worked the piece of ground between history of art, literature, science and religion. Saxl's own research agenda was multifarious, the history of astrology, of mythology, in particular the research into illuminated astrological and mythological manuscripts of the Middle Ages, gleaned from archives all over Europe and published in three comprehensive Verzeichnisse. He further worked on religions of classical antiquity, the transition from pagan to Christian traditions, Mithras as well as art historical topics, Bellini, Titian. His life-long great admiration for Rembrandt found expession in a number of publications. 17th century art history, English medieval sculpture and his last great interest, seals, completed his scholarly output. But next to these research topics his achievements in the fields of organization were the area in which Saxl truly excelled. Warburg, although he spoke of him as the "junior partner", admired his scholarly honesty and thoroughness, but ultimately underestimated his achievements in administration and organization; these alone made it possible that the private library of Warburg could be consolidated into a internationally approved institute of teaching and research in Germany, and then in Great Britain. As Warburg's successor Saxl both kept as close as possible to Warburg's method as well as break fresh ground. Saxl was a truly original thinker, a congenial teacher, very demanding to his students and colleagues, but also fiercely supportive, for instance, to Roger Hinks, when he lost his post at the British Museum in the course of the affair of the cleaning of the Elgin Marbles. He employed Anthony Blunt as editor of the Warburg Institute publications, he brought Ernst H. Gombrich from Vienna to London in 1936. He was a great example to the young art historian John Pope-Hennessy, later Director of the Victoria and Albert Museum and the British Museum. Today, the Warburg Institute is a post-graduate research institute specializing in researching cultural and intellectual history, a forum for scholars and students. The fact that teaching and research could be kept up in Hamburg until 1933 and resumed in London from 1934 onward, speaks for the personal commitment of the employees and above all for Saxl;s intellectual courage and sense for practical solutions. His unstinting effort and dedication were certainly reasons for Saxl's early death at 58 years of age.